2020
DOI: 10.3389/fonc.2020.01662
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pre-operative Measurements of Tumor Size by MRI Methods as Survival Predictors in Wild Type IDH Glioblastoma

Abstract: Objective: We evaluate the performance of three MRI methods to determine non-invasively tumor size, as overall survival (OS) and Progression Free Survival (PFS) predictors, in a cohort of wild type, IDH negative, glioblastoma patients. Investigated protocols included bidimensional (2D) diameter measurements, and three-dimensional (3D) estimations by the ellipsoid or semi-automatic segmentation methods. Methods: We investigated OS in a cohort of 44 patients diagnosed with wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
4
11
1
Order By: Relevance
“…Regarding the tumor localization, Flores in a cohort of 44 patients, including only cases of GBM according to the WHO classification from 2021 and very close to our demographic characteristics, found that the majority of tumors (59.1%) are located in the right cerebral hemisphere, and the most common localization relative to the lobe is the frontal (29.5%), followed by temporal and parietal with 25%, and the rarest localization in the occipital lobe [ 22 ]. In another study, similar in volume and gender distribution but with a significantly lower mean age (49.05 years), Abd-Elghany found that again the most common site of GBM was in the frontal lobe, followed by the temporal, parietal, occipital lobes, and most rarely-subtentorial [ 23 ].…”
Section: Discussionsupporting
confidence: 54%
“…Regarding the tumor localization, Flores in a cohort of 44 patients, including only cases of GBM according to the WHO classification from 2021 and very close to our demographic characteristics, found that the majority of tumors (59.1%) are located in the right cerebral hemisphere, and the most common localization relative to the lobe is the frontal (29.5%), followed by temporal and parietal with 25%, and the rarest localization in the occipital lobe [ 22 ]. In another study, similar in volume and gender distribution but with a significantly lower mean age (49.05 years), Abd-Elghany found that again the most common site of GBM was in the frontal lobe, followed by the temporal, parietal, occipital lobes, and most rarely-subtentorial [ 23 ].…”
Section: Discussionsupporting
confidence: 54%
“…Preoperative tumor volumes volumetrically were assessed based on gadolinium-enhanced T1-weighted MRI using commercially available software (TumorTracking Tool, IntelliSpace Portal 5.0, Philips, the Netherlands). In accordance to Flores et al [ 19 ], a cutoff value of 60 mL of tumor volume was chosen in order to analyze for a potential correlation between tumor volume and PBT. Every neurosurgeon in charge fulfilled the requirements for Neuro-Oncology Centers certificated by the German Cancer Society.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, GBM patients have a meagre immune response by promoting a tumor-induced anti-inflammatory response and creating an immunosuppressive environment for tumor growth [ 1 , 2 ]. Consequently, regardless of how rapidly the diagnosis is determined and how the treatment is initiated, the overall survival is extremely low, i.e., only 12–18 months [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding GBM prognosis, several markers have been taken into consideration. According to the WHO classification, there are two subtypes of GBM depending on their respective genetic features, particularly, the presence or absence of IDH mutations: primary and secondary GBMs [ 3 , 4 ]. On the one hand, primary GBMs usually occur in elderly patients, have no precursor benign or malignant lesions and generally yield a worse prognosis [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation